2022
DOI: 10.3765/salt.v31i0.5107
|View full text |Cite
|
Sign up to set email alerts
|

Imprecision, personae, and pragmatic reasoning

Abstract: Recent work at the interface of semantics and sociolinguistics showed that listeners reason about the semantic/pragmatic properties of linguistic utterances to draw social inferences about the speaker (Acton and Potts 2014; Beltrama 2018; Jeong 2021). These findings raise the question of whether reverse effects exist as well, i.e., whether (and how) social meanings can also impact the interpretation of semantic/pragmatic meanings. Using (im)precision as a case study, we provide experimental evidence that (i) n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
11
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
1
1

Relationship

0
5

Authors

Journals

citations
Cited by 5 publications
(11 citation statements)
references
References 43 publications
0
11
0
Order By: Relevance
“…On the other hand, and more centrally for our purposes, it's been shown that the social information available in the context affects the computation of the level of precision with which a numeral is interpreted. In particular, Beltrama & Schwarz (2021) provide evidence that comprehenders reason about the persona embodied by the speaker in inferring the range of facts compatible with a numeral description. Evidence supporting this claim is based on participants' indirect judgments about whether a certain fact is a likely candidate for being the one the numeral utterance was aiming to describe.…”
Section: Introductionmentioning
confidence: 92%
See 2 more Smart Citations
“…On the other hand, and more centrally for our purposes, it's been shown that the social information available in the context affects the computation of the level of precision with which a numeral is interpreted. In particular, Beltrama & Schwarz (2021) provide evidence that comprehenders reason about the persona embodied by the speaker in inferring the range of facts compatible with a numeral description. Evidence supporting this claim is based on participants' indirect judgments about whether a certain fact is a likely candidate for being the one the numeral utterance was aiming to describe.…”
Section: Introductionmentioning
confidence: 92%
“…In a similar vein, a growing amount of work has been shedding light on the impact of social information on the processes involved when interlocutors resolve, and ultimately exchange, meaning in conversation. On an empirical level, it's been shown that pragmatic reasoning is impacted by a range of different social factors -e.g., politeness considerations (Bonnefon, Feeney & Villejoubert 2009;Yoon, Tessler, Goodman & Frank 2020;Mazzarella, Trouche, Mercier & Noveck 2018); affect (Kao, Wu, Bergen & Goodman 2014;Bergen 2016); speaker-specific properties such as linguistic nativeness (Fairchild & Papafragou 2018) and political orientation (Mahler 2020), and broader personae and identity categories (Beltrama & Schwarz 2021; see §2 for further details). Conversely, it has also been shown that comprehenders promptly infer identity and personality features of a speaker from the semantic and pragmatic properties of their utterances (Acton & Potts 2014;Beltrama & Staum Casasanto 2017Acton 2019;Glass 2015;Karawani & Waldon 2017;Jeong 2021;Thomas 2021;Hunt & Acton 2022; see Beltrama 2020 for an overview).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Specifically, our incorporation of persona in the prompt design is inspired by Beltrama and Schwarz (2021). They find that to compute the standard of precision required to interpret numeral expressions, human comprehenders reason about the speaker's social identity, particularly about the persona they embody.…”
Section: Introductionmentioning
confidence: 99%
“…Against this background, our goal is to examine the extent to which pre-trained LMs can "understand" implicit EVAL implicatures. We hypothesized that if pre-trained LMs are cognitively plausible, their performance should align with the human data in Brasoveanu and Rett (2018) and Beltrama and Schwarz (2021), namely: i) there should be no EVAL difference regarding adjective polarity, ii) LMs should predict POS constructions to be the most evaluative, iii) whether LMs consider the relative adjectives to be more or less evaluative than the absolute adjectives depends on construction type, iv) LMs should (at least) show a trend that the chill-persona prompt helps LMs' understanding of implicatures, relative to the nerdy-persona prompt.…”
Section: Introductionmentioning
confidence: 99%